Validation of the EuroQol Five-dimensions - Three-Level Quality of Life Instrument in a Classical Indian Language (Odia) and Its Use to Assess Quality of Life and Health Status of Cancer Patients in Eastern India - Tripathy, Swagata (Indian J Palliat Care, 2015)
BACKGROUND AND OBJECTIVES: The EuroQol five-dimensions – 3-level (EQ5D) is a versatile quality of life (QOL) instrument with five dimensions (mobility, self-care, usual activities, pain/discomfort, and anxiety/depression) and a visual analog scale. It can be used to calculate quality-adjusted life years. We aimed to evaluate the validity, reliability, and responsiveness of an Odia version of EQ5D and to study the QOL of cancer patients in our part of the country as cancer treatment in India still focuses largely on longevity due to scarcity of resources. MATERIALS AND METHODS: The EQ5D tool was translated into Odia language in collaboration with the EQ group. This tool and the World Health Organization-5 (WHO-5) questionnaires were administered to 155 surgical outpatients and 150 cancer patients in two hospitals of Eastern India. The convergent and discriminant validities (construct validity), concurrent validity, reliability (test-retest method of administering the tool to a part of the population after 7–14 days), and the internal consistency (Cronbach's alpha) were measured using preestablished hypotheses. The data from the cancer patients were analyzed separately. RESULTS: The QOL worsened with age and was worse in cancer patients proved that the tool had good construct validity. The Anxiety Depression dimension had good correlation with all the dimensions WHO-5 (rho > 0.4) indicating a good concurrent validity. Internal consistency and reliability of the tool were good (Cronbach's alpha > 0.7). Cancer patients had a poor QOL (mean EQ5D index 0.37SD 0.4) with male patients, patients with Grade II cancer or referred for pain care services and those with living spouses reporting worse QOL. CONCLUSIONS: The Odia version of the EQ5D has good reliability and validity for the measurement of health status in cancer and outpatient department patients. Cancer patients in this part of the country have a poor QOL and may need a closer look at pain management and improved societal support systems.